Polygamy in the Lens of Generation Z: A Communication Psychology Perspective - Rustandi, Apriya Maharani; Suhendar, Aris; Dalimunthe, Maulana Andinata (Komunika, 2024)
Generation Z, who grew up in the digital era and globalization, faces dynamics in marriage issues that are increasingly complex and diverse, one of which is the issue of polygamy. Therefore the aim of this research is to understand how polygamy is viewed by individuals in Generation Z from a psychological perspective. This research is a quantitative descriptive study with a survey approach using a Likert scale as a way to view the psychometric scale. The results of this research show that Generation Z does not experience high levels of anxiety in facing the issue of polygamous marriage emotionally and psychologically. In the emotional variable, (48%) said it was sufficient, while physiological (42.40%). Overall, this research shows an appropriate reference point for further research by identifying the sources and factors of Generation Z's lack of anxiety regarding the issue of polygamy